A systematic literature review of virtual reality in tourism marketing using a mixed method - Varun Kumar; Bijay Prasad Kushwaha (Cogent Business & Management, 2025)
Virtual reality (VR) is emerging as a revolutionary technology within the tourism sector. It provides immersive experiences that alter how tourists investigate, organize, and interact with diverse destinations. There is an absence of a comprehensive literature review on applications of VR in tourism marketing that consolidates and summarizes previous research findings. Therefore, this research seeks to undertake a systematic literature review of the virtual reality research in tourism marketing, utilizing the TCCM framework and bibliometric analysis, and proposes future research avenues. The corpus of literature is extracted from both the Scopus and Web of Science databases to include scholarly articles. The Bibliometrix R package is employed to merge both datasets and conduct analysis. The results reveal that the predominant themes in the discourse surrounding VR in tourism marketing encompass the virtual world, mental imagery, wearable augmented reality, virtual tourism, and the telepresence model. The most prevalently used theories are Stimulus-Organism-Response Theory, Process Theory, Protection Motivation Theory, and Flow Theory. Similarly, prior investigations within this field employ quantitative, qualitative, and experimental methodologies. Future research avenues are delineated based on thematic clusters and the outcomes derived from the TCCM framework.